2016
DOI: 10.1111/hel.12311
|View full text |Cite
|
Sign up to set email alerts
|

The Upregulation of TRAF1 Induced by Helicobacter pylori Plays an Antiapoptotic Effect on the Infected Cells

Abstract: H. pylori infection induces the overexpression of TRAF1 in gastric epithelial cells. The upregulation of TRAF1 plays an antiapoptotic role in H. pylori -infected gastric cells and may contribute to the gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…There is no doubt that TRAF1 is an important factor for cancer progression. Many researchers have found that TRAF1 is upregulated in blood and solid tumors including stomach, ovarian, nasopharyngeal and skin cancers . TRAF1 is an important anti‐apoptotic factor in the NF‐κB and JNK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that TRAF1 is an important factor for cancer progression. Many researchers have found that TRAF1 is upregulated in blood and solid tumors including stomach, ovarian, nasopharyngeal and skin cancers . TRAF1 is an important anti‐apoptotic factor in the NF‐κB and JNK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed that the expression of TRAF1 in response to H. pylori infection in gastric epithelial cells was mainly regulated by the activation of NF-kB. In addition, upregulation of TRAF1 plays an antiapoptotic role in H. pylori-infected gastric cells (50). Using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, we found that TRAF1 also promoted anti-apoptosis activity via inducing the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 87%
“…The up-regulation of TRAF1 inhibited cell apoptosis and increased the viability of gastric epithelial cells infected with H. pylori . We also determined that H. pylori infection significantly enhanced the formation of the antiapoptotic complex containing TRAF1, TRAF2, cIAP1, and cIAP2, which might play a major role in suppressing the activation of caspase-8 and in inhibiting cell apoptosis[12]. …”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of TRAF1 inhibited cell apoptosis as well as increased the viability of infected cells, which suggested that TRAF1 is an important protein that contributes to the pathogenesis of H. pylori- related gastric cancer[12]. Interestingly, several studies have shown that TRAF1 could be transformed into a pro-apoptotic form after cleavage by caspase-8 in the presence of Fas ligand or TNF-α-induced apoptosis[13-15].…”
Section: Introductionmentioning
confidence: 99%